Rediscovery of Siphonops annulatus (Mikan, 1820) (Amphibia: Gymnophiona: Siphonopidae) in the state of Pará, Brazil, with an updated geographic distribution map, and notes on size and variation - Adriano Maciel; Henrique Costa; Leandro Drummond; Jerriane Gomes; Annelise D’Angiolella (Check List, 2013)
Siphonops annulatus has a wide distribution in South America. Here we provide a new geographic distribution map for this species and two new records from the state of Pará, Brazil, from where it has not been reported since 1876. A specimen collected in the municipality of Senador José Porfírio is the largest specimen of S. annulatus ever recorded.